Source Base of the Research of Organization of Pedagogical Process at the Evening General Educational School of Ukraine (1943-1991) - Stoliar, Valentyna (Pedagogical Discourse, 2013)
The source base of the research of the problem of organization of pedagogical process at the evening general educational school of Ukraine (1943-1991), which is represented by the documents and materials from the state achieves; materials of those days pedagogical periodicals has been determined in the article («Biology at School», «Evening Secondary School»,«Teaching of Pupil», «Geography at School», «Foreign Language at School», «Literature at School», «Mathematics at School», «Peopleʼs Education», «Teaching of History at School», «Soviet Education», «Soviet School», «Russian Language at School», «Soviet Pedagogics», «Physics at School», «Physical Culture at School», «Chemistry at School» and others.). The documents of the funds (f.1, f.2, f.166, f.582, f.2605, f.5111) of the Central State archives of higher organs of power and management of Ukraine have been fully analyzed. The role of the sources, their informative means, that allow to clear out some problems of the research in the more flexible way, have been characterized.